An overview of surgery-first approach: Recent advances in orthognathic surgery - Sharma, Vipul Kumar (J Orthod Sci, 2015)
The disadvantages of having orthodontic interventions both before and after orthognathic surgery include a long treatment time of 7–47 months and temporary worsening of facial appearance. Nowadays, the concept of surgery-first, followed by orthodontic treatment is applied to orthognathic surgery cases in different orthodontic centers in the world. This concept and technique is called “surgery-first-orthognathic-approach” or “surgery-first approach” (SFA) rigid fixation (skeletal anchorage system) of the bony segments and regional acceleratory phenomenon were keys to broad implementation of the SFA. This article is intended to provide an overview of SFA including indications, general and specific guidelines, different protocol variations, success rate and potential problems.